Implementing person centred dementia care: a musical intervention - Argyle, Elaine; Kelly, Tony (Emerald, 2015)
Purpose - Recent years have seen the advocacy of person centred approaches to dementia care. An important component of this approach has been the use of arts in the promotion of health and wellbeing. However, relatively little attention has been given to the barriers and facilitators experienced in trying to implement these types of interventions in a dementia care setting. It is therefore the purpose of this article to help to redress this neglect by examining the process of implementing a personalized musical intervention for clients of a specialist dementia home care service.